2019
DOI: 10.1002/hep.30534
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Ammonia in Patients With Cirrhosis

Abstract: Ammonia is thought to be central to the pathogenesis of hepatic encephalopathy (HE), but its prognostic role in patients with cirrhosis and acute decompensation is unknown. The aims of this study were to determine the relationship between ammonia levels and severity of HE and its association with organ dysfunction and short‐term mortality. We identified 498 patients from two institutions as part of prospective observational studies in patients with cirrhosis. Plasma ammonia levels were measured on admission an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 32 publications
5
92
0
5
Order By: Relevance
“…A reduction in ammonia level was associated with improved survival, confirming it as a potential therapeutic target. Classically in urea cycle disorders ammonia levels above 200 μmol/L were considered a poor prognostic factor [18], but in this study in cirrhotics even ≥79.5 μmol/L was associated with increased mortality, indicating an additional role of ammonia in dictating clinical outcomes [11].…”
Section: The Physiopathology and Increased Morbidity-mortality With Tmentioning
confidence: 53%
See 2 more Smart Citations
“…A reduction in ammonia level was associated with improved survival, confirming it as a potential therapeutic target. Classically in urea cycle disorders ammonia levels above 200 μmol/L were considered a poor prognostic factor [18], but in this study in cirrhotics even ≥79.5 μmol/L was associated with increased mortality, indicating an additional role of ammonia in dictating clinical outcomes [11].…”
Section: The Physiopathology and Increased Morbidity-mortality With Tmentioning
confidence: 53%
“…Early studies had shown a correlation of levels of ammonia and worsening HE up to two times the upper limit of normality [6]. Further studies have not only cemented this correlation but have shown a more intricate relationship [10,11]. It can predict the risk and frequency of HE episodes [12].…”
Section: Correlation Of Levels and Development Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…Acute-on-chronic liver failure (ACLF) is characterized by high shortterm mortality, and outcomes depend on the type of organ failure. (1,2) The study by Shalimar et al (3) is a welcome addition to the literature regarding hyperammonemia and prognosis in cirrhosis, acute decompensation, or ACLF. The authors studied the relation of serum ammonia with hepatic encephalopathy, organ failure, and mortality in a cohort of 498 patients.…”
Section: To the Editormentioning
confidence: 98%
“…In this context, a plethora of parameters have already been identified that seem to improve preoperative risk assessment of patients undergoing liver resection. (2)(3)(4)(5) Indeed, the combination of preoperative liver function assessment might be beneficial to further characterize patients' risk for adverse postoperative outcome. However, the central aim of the presented study was to define a preoperative parameter that is easily assessable and highly standardized to provide a reliable and internationally available tool.…”
mentioning
confidence: 99%